Eddy Current Testing in Service of the Boiler Heating Surface Tube Elbow in Thermal Power Plants. Issue 1 (October 2020) - Liu, Yunlong; Xie, Ameng; Shen, Dingjie; Yang, Xiangwei
Abstract: According to the characteristics of closed ends, tight tube screen and narrow testing spaces of the eddy current testing in service of the boiler heating surface tube elbow in thermal power plants, an external placed saddle eddy current testing probes which could be used to test the small diameter austenitic stainless steel tube elbow was designed. Then the comparative sample tube was processed in accordance with the eddy current testing technical standards. Through the sample testing and the applications in thermal power plants, the results show that the designed saddle-shaped eddy current detecting probe device has high detection sensitivity and reliability for linear defects above 0.2 mm and hole defects above Φ1.4 mm. It can realize the non-destructive testing in service of the austenitic stainless steel tube elbow, which has more serious oxidation, corrosion and more focused stress.